Cytokines and chemokines associated with Treg/Th17 response in chronic inflammatory periapical disease - TOLEDO,André Oliveira Naufel de (2019)
Abstract Cytokines and chemokines have a fundamental role in the maintenance of inflammation and bone response, which culminate in the development of chronic periapical lesions. Regulatory (Treg) and Th17 cytokines play a key role in regulating the immune response involved in this process. The aim of this study was to investigate the role of Treg and Th17 cells in chronic inflammatory periapical disease, by comparing the expression of the immunoregulatory mediators TGF-β, IL-10, CCL4, and the proinflammatory IL-17 and CCL20 in the periapical tissue of teeth with pulp necrosis, with and without associated chronic lesions. Eighty-six periapical tissue samples were obtained from human teeth. The samples were divided into three groups: pulp necrosis with a periapical lesion (n=26); pulp necrosis without a periapical lesion (n=30), and control (n=30). All samples were submitted to histopathological analysis and cytokine and chemokine measurement through ELISA. Statistical analyses were done with Kruskal-Wallis and Mann-Whitney tests and Spearman correlation. The group with pulp necrosis and a periapical lesion showed a higher expression of CCL4 and TGF-β in comparison with pulp necrosis without a lesion. CCL20 was higher in the group with a periapical lesion when compared to the control. In all groups there was a weak positive correlation between IL-17/CCL20, IL-10/CCL4, and IL-17/TGF-β. Both types of cytokines, pro-inflammatory and immunoregulatory, occur simultaneously in periapical tissue. However, a rise in immunosuppressive cytokines and chemokines (CCL4 and TGF-β) in periapical lesions suggests a role of these cytokines in stable periapical disease.